Assessment of Population Mean MAPs for Activation of Cochlear Implant Sound Processors Compared With Behavioral Programming - Biever, Allison; Bishop, Grayson A; Lupo, J Eric; Kelsall, David C (Otology & neurotology, 2025)
Population mean MAPping is a recently developed tool based on normative MAP data from a large cohort of CI recipients. Compared with conventional methods, this novel technique relies less on recipient feedback. There is limited literature about the impact of population mean MAP activation on patient outcomes. The objective of this study was to compare audiological outcomes and MAP levels between CI recipients whose devices were programmed at activation using a population mean MAP or the traditional behavioral threshold and loudness scaling method. Retrospective chart review. Single CI center. One hundred seventy-eight adult CI recipients of CI632. Population mean compared with behavioral threshold and loudness scaling MAP activation. Preoperative and postoperative consonant-nucleus-consonant (CNC) scores assessed at 3, 6, and 12 months; MAP programming characteristics. Postoperative CNC scores improved significantly at all time points from preoperative baseline in both groups who had their MAPs programmed using the population mean or the behavioral programming approach [F (2, 89) = 5.93, P < 0.01]. CNC performance was not affected by the method of activation, or the combined impact of time point and programming method. However, subjects in the population mean group achieved MAP stability more quickly compared with subjects in the behavioral programming group. Recipients activated with population mean demonstrated equivalent CNC scores to those of recipients activated using traditional behavioral workflows. The quicker MAP stabilization in the population mean group can reduce the clinical needs of CI recipients.